Emerging Bismuth Chalcogenides Based Nanodrugs for Cancer Radiotherapy - Huang, Jia; Huang, Qiong; Liu, Min; Chen, Qiaohui; Ai, Kelong (Frontiers in Pharmacology, 2022)
Radiotherapy (RT), as one of the main methods of clinical tumor treatment, has been applied to the treatment of most solid tumors. However, the effect of RT is compromised by the radiation resistance of tumor hypoxic environment and non-specific damage caused by high-dose radiation. Bismuth chalcogenides (Bi2X3, X=S, Se) based nanodrugs have attracted widespread attention as highly efficient radiosensitizers due to their high photoelectric effect and excellent biocompatibility. More importantly, specially designed nanocomposites can effectively alleviate the radiation resistance of tumor tissues. Here, for the first time, we systematically summarize the latest progresses of Bi2X3 nanodrugs to enhance RT by alleviating the hypoxic tumor microenvironment. These emerging Bi2X3 nanodrugs mainly include three aspects, which are Bi2X3 nanocomposites with high-efficient O2 supply, non-O2-dependent Bi2X3 nanocomposites RT enhancers, and Bi2X3 nanocomposites-based photothermal enhanced RT. These Bi2X3 nanodrugs can effectively overcome the RT resistance of tumor hypoxic microenvironment, and have extremely high therapeutic effects and clinical application prospects. Finally, we put forward the challenges and prospects of Bi2X3 nanomaterials in the field of RT.